Do tax cuts Increase consumption? An experimental test of Ricardian Equivalence - Thomas Meissner; Davud Rostam-Afschar (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
This paper tests whether the Ricardian Equivalence proposition holds in a life cycle consumption laboratory experiment. This proposition is a fundamental assumption underlying numerous studies on intertemporal choice and has important implications for tax policy. Using nonparametric and panel data methods, we find that the Ricardian Equivalence proposition does not hold in general. Our results suggest that taxation has a significant and strong impact on consumption choice. Over the life cycle, a tax relief increases consumption on average by about 22% of the tax rebate. A tax increase causes consumption to decrease by about 30% of the tax increase. These results are robust with respect to variations in the difficulty to smooth consumption. In our experiment, we find the behavior of about 62% of our subjects to be inconsistent with the Ricardian proposition. Our results show dynamic effects; taxation influences consumption beyond the current period.
Keywords: D91; E21; H24; C91; 330; Ricardian Equivalence; Taxation; Life Cycle; Consumption; Laboratory Experiment